THE PURPOSE OF LIFE - S, M.Alagesan,; Kumar, Horizan Prasanna; Tong , 3Chong Seng; Veettil, Roy P (International Journal of Psychosocial Rehabilitation, 2020)
This study tries to focus on how an individual gets his/her purpose in life. Instead of telling the importance we have to start making a way or creating or building a new direction for an individual to easily access their purpose in life without making confusing by showing the complexity of this issue. All of us have to start working on this issue because our brothers and sisters are dying with enough knowledge of purpose but without living it. One can be 100% sure, if individuals couldn’t get their purpose in life, the percentage of having satisfaction in their life becomes very low. All of us have to stand together, this is our issue. In general, many scholars gave much information about the importance of purpose in life but they are not able to create, build, and make a way of getting it. The author believes there should be a way and in addition to that, this study suggests that all of us including the scholars have to focus on answering how an individual’s able to access their purpose in life instead of telling how important it is.